Artificial intelligence-based game design and control using brain signals - Lim, Evan Cheng Yi (Nanyang Technological University, 2022)
As technology continues to flourish, industries that leverage technology continues to grow positively. One of such industry is the gaming industry which has been growing significantly and established eSports tournaments to allow friendly international competition between players. Game developers have also been actively looking for new input devices in hopes to enhance the player’s gameplay experience. Some examples of input devices for gaming are the virtual reality headset, driving steering wheel set, and joysticks. Aside from the mentioned, game developers are also looking into the usage of Electroencephalogram (EEG) as a new communication pathway between a player’s brain and the gaming device, Hence, forming a Brain-Computer Interface (BCI). For this project, a MUSE 2 headset will be used to enhance the player’s gameplay experience of a self made 3D game called “Tower of Proof”. The Player’s concentration level will be measured using the MUSE 2 headset along with a python script which helps to determine when the player is concentrated.